(untitled) (Journal of Comparative & International Higher Education, 2024)
While numerous case studies examined the effect of COVID-19 on international students, there has been limited scholarly attention on comprehensive crisis management strategies. Comparing crisis management strategies between the United States (US) and South Korea, this research aimed to explore international student crisis management strategies practiced at the onset of COVID-19, along with the stated rationales for the strategies. This study collected 119 news articles from the US and 90 from South Korea about ‘COVID-19’ and ‘international students’ from January to September 2020. Prominent rationales stated in both the US and Korea were students’ Health & Security and Humanitarianism & Human Rights. Korean Universities prioritized moral rationales over Economic or Political benefits of recruiting international students, which was assumed to be a practice of East Asia’s collectivist and Confucian culture. Also, Immigration & Legal Support was prioritized among universities in the US, where the government took relatively aggressive measures on visa restrictions. Despite growing interest in how universities should take the role of providing public good in higher education internationalization; Cosmopolitan Learning & Campus Diversity rationales were emphasized in neither countries.